The Role Of The Police In Completing The Practice Of Domino Card Gaming - Raflin Wantu (Estudiante Law Journal, 2020)
Abstract: The implementation of this research is to find out and analyze the role of the police in dealing with domino card gambling practices and to find out the factors that hinder the police in dealing with domino card gambling practices and the type of research is empirical research. The results show that the role of police in dealing with domino card gambling practices still has obstacles in the form of an approach to the community, one of which is the lack of socialization from the police even though it is carried out using pre-emptive and repressive measures. Meanwhile, the factors that hinder the police in dealing with the practice of domino card gambling are that the police are still difficult to track down the places where gambling practices occur. carried out by the community, the low level of public awareness is based on the consequences of unsupportive Economic, Knowledge, Entertainment and C,ultur,e and Community Environment factors.  Keywords: The Role of the Police, Domino's Card Gambling